设S=13+23+33+…+n3……………………………………………………….(1) 有S=n3+(n-1)3+(n-2)3+…+13……………………………………………...(2) 由(1)+ (2)得:2S=n3+13+(n-1)3+23+(n-2)3+33+…+n3+13 =(n+1)(n2-n+1) + (n+1)[(n-1)2-2(n-1)+22) + (n+1)[(n-2)2-3(n-2)+32) + . . . + (n+1)(12-n(n-n+1)(n-n+1+ n2) 即2S=( n+1)[2(12+22+32+…+n2)-n-2(n-1) -3(n-2)-…-n (n-n+1)] ………………...(3) 由12+22+32+…+n2=n(n+1)(2n+1)/ 6代入(2)得: 2S=(n+1)[2n(n+ 1)(2n+1)/6-n-2n-3n-…nn+2×1+3×2+…+n(n-1)] =(n+1)[2n(n+1)(2n+1)/6-n(1+2+3+…n)+(1+1)×1+(2+1)×2+…+(n-1+1)(n-1)] =(n+1)[2n(n+1)(2n+1)/6-n2 (1+n)/2+12+1+22+2+…+(n-1)2+ (n-1)] =(n+1)[2n(n+1)(2n+1)/6-n2(1+n)/2+12+22+…+(n-1)2+1 +2+…+ (n-1)] ……...(4) 由12+22+…+(n-1)2= n(n+1)(2n+1)/6-n 2,1+2+…+(n-1)=n(n-1)/2代入(4)得: 2S=(n+1)[3n(n+1)(2n+1)/6-n2+n(n-1)/2 =n2(n+1)2/2 即S=13+23+33+…+n3= n2(n+1)2/4 =n的平方*(n+1)的平方除以4 因为n=100.所以。原式=25502500
希望采纳